Scoliid Wasps of Florida, Campsomeris, Scolia and Trielis spp. (Insecta: Hymenoptera: Scoliidae) - E. E. Grissell (EDIS, 2007)
EENY-409, an 8-page illustrated fact sheet by E. E. Grissell, is part of the Featured Creatures collection. It describes a family of brightly patterned, stout-bodied wasps which are parasitoids of scarab beetle larvae. Includes sections on synonymy, biology, hosts, identification. Includes Key to Nearctic Genera and Species of Scoliidae and selected references. Published by the UF Department of Entomology and Nematology, June 2007.